Análise das propriedades de pisos de concreto lapidado com diferentes tratamentos superficiais - Takeda, Nereu Teixeira Rodrigues (Universidade do Vale do Rio dos Sinos, 2025)
Grinding and abrasive polishing are essential processes in the treatment of concrete surfaces, as they improve wear resistance, reduce roughness, and increase durability. These techniques have been applied to indoor concrete floors, aiming to meet performance requirements in commercial, corporate, and residential environments. The efficiency of surface treatments is determined by physical, mechanical, and chemical properties that directly influence the service life of the material. The main objective of this study was to analyze the properties of indoor concrete floors subjected to different levels of abrasive polishing, focusing on their resistance, functional performance, and durability. An experimental program was carried out with 12 concrete slabs, of which 10 received surface treatments and 2 were used as references. After 28 days of wet curing, diamond abrasives, latex-based cement, silicate-based surface hardener, sealant, and polishing pads with progressive grit sizes (#200, #400, #800, #1500, and #3000) were applied. The effectiveness of the treatments was assessed through standardized tests, including abrasion resistance, gloss measurement (GU), surface roughness, hardness, chemical resistance, and stain resistance. The results showed significant improvements in abrasion resistance, with wear reduction of up to 24.86%, progressive increases in gloss, reaching 76.86 GU in the high-gloss finish (#3000), and reductions in surface roughness to 0.85 µm. Hardness increased by up to 82.30% compared with the reference samples, while chemical resistance was classified as Class A. In the stain resistance tests, the highest polishing levels achieved the maximum cleaning classification (Class 5). It was concluded that abrasive polishing of indoor concrete floors provided significant physical, mechanical, and chemical performance improvements, directly contributing to increased durability and reinforcing the importance of choosing appropriate surface treatments.
Keywords: Polimento de concreto; Tratamentos de superfície; Resistência à abrasão; Durabilidade; Propriedades de superfície; Concrete polishing; Surface treatments; Abrasion resistance; Durability; Surface properties; ACCNPQ::Engenharias::Engenharia Civil